Cooling performance of Joule Thomson coolers in 300 K -50 mK cryochain demonstration for ATHENA X-IFU. (April 2019) - Shinozaki, K; Tokoku, C; Yamamoto, R; Minami, Y; Yamasaki, N Y; Mitsuda, K; Nakagawa, T; Duval, J M; Prouvé, T; Charles, I; Lé Du, M; Andre, J; et al.
Abstract: The cooler system for the ESA X-ray astronomical mission ATHENA X-IFU instrument is being studied, and a demonstration cooling test has been performed by integrating the mechanical coolers (double-stage Stirling cooler = 2ST, 4K-class and 1K-class Joule Thomson coolers = 4K-JT and 2K-JT) provided by JAXA with the coolers (15K-class pulse tube cooler = PT15K and 50mK hybrid cooler) provided by CEA into the cryostat. This paper describes the measured cooling performances of these Joule Thomson coolers under successful integration with the 50mK hybrid cooler and the pulse tube cooler. The demonstration test is proceeded under the international framework of ESA Core Technology Program (CTP) for a detector cooling system demonstration for ATHENA, and should provide valuable insight for other future space missions such as SPICA and LiteBIRD.